Students’ English business communication self-efficacy and their career aspirations - Hartono Hartono; Huyi Intan Sari (Universitas Islam Sultan Agung, 2020)
Self-efficacy, which is defined as people’s judgment on their ability to carry out tasks and exercise control over events, is believed to be determinant in the success of learning and career aspiration. The study was conducted to measure students’ self-efficacy in making English business communication, their career aspiration, and the relationship between them. Sixty one students served as the respondents for the study. Data were collected by using Likert-typed questionnaires after students attended an ESP designed to improve their English business communication skills. It found that students had high self-efficacy in making English business communication and high career aspiration. Between these variables lies a significant positive correlation in moderate level (0.611).